The little book of skin care : Korean beauty secrets for healthy, glowing skin - Cho, Charlotte (William Morrow, an imprint of HarperCollinsPublishers, 2015)
It all starts with your skin! In Korea, healthy, glowing skin is the ideal form of beauty, achievable by anyone--and this skin-first philosophy has taken the world by storm. In this book, Charlotte Cho, of leading beauty/lifestyle website Soko Glam, guides you through the celebrated Korean ten-step skincare routine--and far beyond--for the clearest and most radiant skin of your life, with step-by-step tutorials, skin-care tips, advice on products at all price levels, and exclusive interviews with beauty experts around the world. You'll love pampering your skin at home and learning the secrets behind the "no-makeup makeup" look we've seen and admired on women in the streets of Seoul. With the knowledge of an expert and voice of a trusted friend, Charlotte's personal tour through Korean beauty culture will help you find joy in the everyday beauty routines that will transform your skin.--